A pilot study to investigate the measurement of immunoglobulin A in Welsh Cob and Welsh Pony foals' faeces and their dam's milk. Issue 4 (3rd July 2020) - Riley, CB; Jenvey, CJ; Baker, FJ; Corripio, A
ABSTRACT: Aims: To determine if an ELISA for measurement of IgA in equine serum could be used to measure concentrations of IgA in foal faeces and to determine correlations with concentrations in the milk of the dam. Methods: Faeces from 20 Welsh Cob and Welsh Pony foals and milk from their dams were collected within 12 hours (Day 0) and at 6 days after parturition (Day 6). On Day 6, faeces could not be collected from 2/20 foals, and milk samples could not be collected from 3/20 mares. An equine IgA ELISA validated for serum and plasma was used to measure concentrations of IgA in all samples in triplicate. The precision of the assay for each sample type was determined using modified CV. Results: IgA was not detectable in 7/20 Day 0 faecal samples and in 2/18 Day 6 faecal samples. For samples with detectable IgA, the mean modified CV was 10.5 (95% CI = 6.0–15.0)% for Day 0 faecal samples, and was 6.8 (95% CI = 4.3–9.4)% for Day 6 faecal samples. Median concentrations of IgA in faeces on Day 0 were lower than concentrations on Day 6 (0.7 mg/g vs . 37 mg/g dry matter; p = 0.003). Concentrations of IgA in milk and faeces on Day 6 were statistically correlated (r = 0.59; p = 0.006). Conclusions and clinical relevance: The IgA ELISA showed acceptable precision when used to estimate concentrations of IgA in foal faeces during the first week of life, but IgA could not be detected in 37% of meconium samples collected on Day 0. This assay may be useful for investigation of the role of maternal milk IgA in the gastrointestinal tract of neonatal foals, but further assessment of both accuracy and precision of the ELISA is required.